International taxation and multinational firm location decisions - Salvador Barrios Cobos; Harry Huizinga; Luc Laeven; Gaëtan J.A. Nicodème (Center for Economic Studies and ifo Institute (CESifo), 2008)
Using a large international firm-level data set, we estimate separate effects of host and parent country taxation on the location decisions of multinational firms. Both types of taxation are estimated to have a negative impact on the location of new foreign subsidiaries. In fact, the impact of parent country taxation is estimated to be relatively large, possibly reflecting its international discriminatory nature. For the cross-section of multinational firms, we find that parent firms tend to be located in countries with a relatively low taxation of foreign-source income. Overall, our results show that parent-country taxation - despite the general possibility of deferral of taxation until income repatriation - is instrumental in shaping the structure of multinational enterprise.
Keywords: F23; G32; H25; R38; 330; Corporate taxation; dividend withholding taxation; location decisions; Unternehmensbesteuerung; Betriebliche Standortwahl; Steuerbegünstigung; Multinationales Unternehmen; Welt